Why do models fail to assess properly the sustainability of duiker (Cephalophus spp.) hunting in Central Africa? - Vliet, N. van; Nasi, Robert (Cambridge University Press, 2008)
Hunting of wildlife in Central Africa is largely considered to be unsustainable. Several studies indicate that most mammal species should already have disappeared from many Central African forests but markets continue to be supplied with bushmeat, with no sign of large scale extinction of the most common species. Most studies of the sustainability of duiker (Cephalophus spp.) hunting in Central Africa are based on the same index of hunting. We illustrate how uncertainty is accumulated in these estimations of sustainability. We show that the results obtained in different sites are not comparable because a variety of methods have been used to calculate the parameters of the model and each of the methods has different sources of error. For the assessment of maximum sustainable harvest for duikers, the studies reviewed differ mainly in the value chosen for the hypothetical adjustment factor, and the method used to calculate the rate of maximum population increase and to estimate duiker population densities. For the assessment of annual hunting offtake the studies differ mainly in the scale at which they were conducted (village or regional), and sampling and extrapolation methods. Without evaluation of accuracy and standardization of methods for the estimation of maximum sustainable harvest and annual offtake, conclusions regarding harvesting based on biological indices should be treated with extreme caution